A girl with developmental delay, ataxia, cranial nerve palsies, severe respiratory problems in infancy—Expanding NDST1 syndrome. Issue 3 (March 2017) - Armstrong, Linlea; Tarailo‐Graovac, Maja; Sinclair, Graham; Seath, Kimberly I.; Wasserman, Wyeth W.; Ross, Colin J.; van Karnebeek, Clara D. M.
Abstract : NDST1 encodes an enzyme involved in the first steps in the synthesis of heparan sulfate chains, proteoglycans that are regulators found on the cell surface and in the extracellular matrix. Eight individuals homozygous for one of four family‐specific missense mutations in the sulfotransferase domain of the enzyme have been described. They have intellectual disability. Some additionally had hypotonia, ataxia. seizures, and/or short stature, but none had history of respiratory problems. No humans with homozygous null mutations are known. ndst1b (orthologous to NDST1) morpholino knockdown in zebrafish (Danio rerio) causes delayed development, craniofacial cartilage abnormalities, shortened body and pectoral fin length. Ndst1 homozygous null mice have craniofacial abnormalities and die within the first 10 h of life of respiratory failure. We report a girl upon whom deep phenotyping, extensive genetic and biochemical investigations, and exome sequencing were performed. She had cranial nerves dysfunction, gastroesophageal reflux, history of a seizure, ataxia, developmental delays, head sparing failure to thrive, and minor malformations including distinctive facial features and a bifid uvula. Compound heterozygous mutations in NDST1 were identified, in the heparan sulfate N deacetylatase domain of one allele and the sulfotransferase domain of the other allele. This report expands the phenotypic spectrum of Ndst1 deficiency in humans. © 2017 Wiley Periodicals, Inc.